Ciclo biológico de biótipos de Digitaria insularis suscetível e resistente ao glyphosate em dois períodos de crescimento. - Ferreira, Silvio Douglas (2016)
This study aimed to evaluate the biological cycle of susceptible biotypes of Digitaria insularis and resistant to glyphosate. The seeds of the biotypes of D. insularis were collected in populations from geographically distant agricultural areas belonging to producers Brejo Paraibano no history of using herbicides, so susceptible's supposed to, and west of Paraná, with a history of resistance. To carry out the evaluations of the growth curves of both experiments the same methodologies were used. The experimental design was a randomized block with four replications. The treatments consisted of plant collections seasons, carried out at regular intervals: 14; 21; 28; 35; 42; 49; 56; 63; 70; 77; 84; 91; 98; 105; 112 and 119 days after emergence (DAE), corresponding to periods of 16 samplings in each period. Biotypes were characterized as follows: AG biotype was considered susceptible, while the CVEL biotypes, ERO and GR were considered resistant and showed FR50 2,7; 3,4 and 7,7 respectively. Between the summer / fall (average temperature of 24,6 °C), the S biotype began issuing tillers and flowering an average of 14 and 21 DAE, respectively, before the resistant biotypes. However, in autumn / Winter (average temperature 19 °C) only biotype R1 was able to develop and finalize the biological cycle. In the summer / autumn period, the S biotype showed the highest absolute growth rate (TCA) at 84 DAE, being 82,3% higher than the resistant biotypes. The higher ratio of leaf area (RAF) was obtained by biotype R3 at 77 DAE, however, could not be verified differences in the relative growth rate (RGR) between biotypes. Biotypes evaluated showed differences during development especially among the phenological phases, so that the susceptible biotype was the earliest and with high reproductive potential